Limiting Resources Define the Global Pattern of Soil Microbial Carbon Use Efficiency - Cui, Yongxing; Hu, Junxi; Peng, Shushi; Delgado‐Baquerizo, Manuel; Moorhead, Daryl L.; Sinsabaugh, Robert L.; Xu, Xiaofeng; Geyer, Kevin M.; Fang, Linchuan; Smith, Pete; Peñuelas, Josep; Kuzyakov, Yakov; et al. (Advanced science, 2024)
Microbial carbon (C) use efficiency (CUE) delineates the proportion of organic C used by microorganisms for anabolism and ultimately influences the amount of C sequestered in soils. However, the key factors controlling CUE remain enigmatic, leading to considerable uncertainty in understanding soil C retention and predicting its responses to global change factors. Here, we investigate the global patterns of CUE estimate by stoichiometric modeling in surface soils of natural ecosystems, and examine its associations with temperature, precipitation, plant‐derived C and soil nutrient availability. We found that CUE is determined by the most limiting resource among these four basic environmental resources within specific climate zones (i.e., tropical, temperate, arid, and cold zones). Higher CUE is common in arid and cold zones and corresponds to limitations in temperature, water, and plant‐derived C input, while lower CUE is observed in tropical and temperate zones with widespread limitation of nutrients (e.g., nitrogen or phosphorus) in soil. The contrasting resource limitations among climate zones led to an apparent increase in CUE with increasing latitude. The resource‐specific dependence of CUE implies that soils in high latitudes with arid and cold environments may retain less organic C in the future, as warming and increased precipitation can reduce CUE. In contrast, oligotrophic soils in low latitudes may increase organic C retention, as CUE could be increased with concurrent anthropogenic nutrient inputs. The findings underscore the importance of resource limitations for CUE and suggest asymmetric responses of organic C retention in soils across latitudes to global change factors. This study investigates the global patterns of CUE and their links to fundamental environmental resources across climate zones. The study clarifies and theorizes resource limitations as the key mechanisms regulating CUE. Results underscore the importance of resource limitations for CUE and suggest asymmetric responses of organic C retention in soils across latitudes to global change factors.